High doses of zoledronic acid induce differential effects on femur and jawbone microstructure - Mariana Q. S. Soares; Jeroen Van Dessel; Reinhilde Jacobs; Gustavo Z. Ferreira; Paulo Sérgio daSilva Santos; Laura F. P. Nicolielo; Marco A. H. Duarte; Izabel R. F. Rubira‐Bullen (Wiley, 2022)
Abstract Objectives The aim of this study is to investigate the long‐term effects on jaw and femur bone induced by oncologic doses of zoledronic acid in a young rat model. Material and Methods Six 12‐week‐old male Wistar rats received zoledronic acid (0.6 mg/kg) and six control rats received saline solution in the same volume. Compounds were administered intraperitoneally in five doses every 28 days. Euthanasia was performed 150 days after therapy onset. After animal sacrifice, their mandibles and femurs were scanned ex vivo using a high‐resolution (14 μm) micro‐computed tomography. Morphometric bone parameters were calculated using CT‐Analyzer (Bruker, Belgium) between the first and second mandibular molars and in the distal femur metaphysis and epiphysis. Results The treatment group as compared to the controls showed a significantly (p < .05) increased bone quantity (↑BV/TV, ↓Po[Tot], ↑Tb.Th), bone density (↑TMD, ↑BMD), and osteosclerosis of the trabecular bone (↓Tb.Sp, ↓Conn.Dn, ↓Tb.Pf, ↓SMI) in all anatomical sites. Bone remodeling suppression due to zoledronic acid treatment was more pronounced (p < .05) in the femoral metaphysis relative to the mandible and epiphysis. The exploratory linear discriminant analysis showed that for the mandible, it was mainly the bone quantity‐related morphometric indices (BV/TV and Tb.Th), while for the femoral epiphysis and metaphysis, it was bone structure‐related (Tb.Pf and Tb.N), which are of primary importance to study the treatment effect. Conclusion High doses of bisphosphonates can differently affect the bone quantity, density, and structure in long bones and jawbones. In the metaphysis, bone changes were primarily concentrated in the region of the growth plate. Future studies may consider the use of bone morphometric indices to evaluate the effect of bisphosphonates.